Effect of the consumption of a fibrous extract of stevia rebaudiana stems on glycemia - Barbosa-Martín, Enrique; Moguel-Ceballos, Juan Eduardo; Rodríguez-Rosas, Cristina; Valencia-Rivera, Dora Edih; Zarza-García, Addy Leticia (Horizonte Sanitario, 2022)
Objective: To evaluate the effect of the ingestion of a fibrous extract of Stevia rebaudiana Bertoni stems on postprandial glycemia levels in healthy subjects. Materials and Methods: Cross-sectional, experimental research, carried out with ethical conditions of consent and reliability, in the Laboratory for the Evaluation of Nutritional Status of the Autonomous University of Carmen. For the clinical and anthropometric assessment of the participants, a medical history and body composition scan were used, respectively. The study population consisted of 16 healthy women with normal body mass indices (20-25 kg/m2). Instruments: a) Clinical-dietetic record and b) Biochemical data obtained from blood sampling obtained at different times. The data analysis was carried out with descriptive statistics. Results: The results shown in the group of participants in this study, it was observed that the mean value of the area under the curve (AUC) of glucose was 709.18 ± 23.60, while that of the fibrous extract of stevia stems was 556.59 ± 50.47 . Conclusions: Stevia rebaudiana stems, due to their dietary fiber content, can be an alternative for the use and revaluation of sustained waste in the circular economy in the development of functional products, giving it an added value that contributes in some way to reducing overweight and obesity, with a hypoglycemic effect in patients with type 2 diabetes mellitus (DM). Keywords: Stevia; Plant Stems; Blood glucose